2006
DOI: 10.2190/fqxn-k610-bny8-uq0l
|View full text |Cite
|
Sign up to set email alerts
|

Social Sensitivity and ACNE: The Role of Personality in Negative Social Consequences and Quality of Life

Abstract: Acne is a biopsychosocial skin condition. Dispositional social sensitivity is an independent psychological factor associated with poorer social functioning and quality of life. Treatment of the acne patient should consider psychosocial factors as well as biological factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
(23 reference statements)
1
21
0
6
Order By: Relevance
“…Acne vulgaris is a common dermatosis and often a cause of diminished quality of life, low self-esteem, as well as negative self- and peer judgements [2,3,4,5,6]. There is a tendency for suicidal ideation as well as depression in patients with acne [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acne vulgaris is a common dermatosis and often a cause of diminished quality of life, low self-esteem, as well as negative self- and peer judgements [2,3,4,5,6]. There is a tendency for suicidal ideation as well as depression in patients with acne [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Prescriptions were individualized to each patient based on personality traits, which also underscores the well-recognized role of psychosomatic factors in acne as well as in the pathogenesis of skin disease [2,3,8,9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krejci Manwaring et al reported a positive correlation between acne severity and poorer quality of life. 30 The majority of our study population consisted of educated and unmarried people belonging to urban areas reflecting that the Quality of Life is affected more in these patients. This could be because of factors like work atmosphere, and pattern of life in cities which make them more concerned about their appearance in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Greater acne severity has been shown to be associated with poorer social outcomes and quality of life [19]. Dermatological-related social anxiety appears to be negatively associated with intention to participate in sport/exercise, self-esteem and dermatological quality of life [18].…”
Section: Discussionmentioning
confidence: 99%